Trends in Reprisals and the Persecution of Opponents of the Regime in Lithuania after 1954 - Burinskaitė, Kristina (Genocidas ir rezistencija, 2012)
The article analyses trends in the repressive policy against opponents of the regime in Lithuania between 1954 and 1990, identifies events and processes which determined changes in this policy, and describes methods applied by the KGB, by paying particular attention to the persecution and reprisals which best reflect developments in the repressive policy. The article specifies activities and the legal basis for imposing punishment by imprisonment or other types of punishment for these activities.Trends in Soviet repressive policy after 1954 were determined by changes in the domestic and international political situation and in the principles of anti-Soviet resistance. The status of Lithuania as a country occupied by the Soviet Union determined the key guideline of the activities of the Lithuanian Communist Party and the KGB of the Lithuanian SSR – to persecute and carry out reprisals against individuals who wished to declare the statehood of Lithuania. The KGB used prevention, discrediting, and propaganda methods in order to discredit, depoliticise, and criminalise this idea and to make it easier to prosecute the said people. This gives us some understanding why certain groups of society – associated with the wish for an independent Lithuania – were distinguished and deliberately persecuted.While the essential features of the repressive policies during the period considered remained the same, there were some obvious differences. Reprisals became selective, i.e. punishment was imposed for certain specific activities. The intensity of reprisals was also salutatory and depended on trends in domestic and international politics and the party position. Although prevention was applied more frequently (statistical data attest to this) as if to show that the regime had changed, this measure was applied as a form of punishment, rather than as a form of re-education. In addition, in this period, the placement of people in psychiatric hospitals was applied as an alternative to imprisonment; death penalties were also carried out.By creating a fictitious legality, the KGB indeed committed crimes against the Lithuanian people, because they implemented the law and interpretations of the law imposed by occupational authorities. Although the government declared that the KGB was changing their working methods and operational principles, the suppressive nature of the KGB did not change, it was only better concealed.
Keywords: Soviet occupation; communist party; KGB; KGB methods; repressions